Thesaurus. Boletín del Instituto Caro y Cuervo: tomo 12 (1957), tomo 13 (1958). - Lope Blanch, Juan M. (Nueva Revista de Filología Hispánica (NRFH), 1964)
Se reseñó: Thesaurus. Boletín del Instituto Caro y Cuervo: tomo 12 (1957), tomo 13 (1958).